Efficient Near Infrared Modulation with High Visible Transparency Using SnO2–WO3 Nanostructure for Advanced Smart Windows. Issue 8 (25th January 2019) - Nguyen, Tam Duy; Yeo, Loo Pin; Kei, Tan Chiew; Mandler, Daniel; Magdassi, Shlomo; Tok, Alfred Iing Yoong
Abstract: Renewable energy technology and effective energy management are the most crucial factors to consider in the progress toward worldwide energy sustainability. Smart window technology has a huge potential in energy management as it assists in reducing energy consumption of indoor lighting and air‐conditioning in buildings. Electrochromic (EC) materials, which can electrically modulate the transmittance of solar radiation, are one of the most studied smart window materials. In this work, highly transparent SnO2 inverse opal (IO) is used as the framework to electrochemically deposit amorphous WO3 layer to fabricate hybrid SnO2 –WO3 core–shell IO structure. The hybrid structure is capable of effective near infrared (NIR) modulation while maintaining high visible light transparency in the colored and bleached states. By varying the initial diameter of the polystyrene (PS) opal template and the WO3 electrodeposition time, optimal results can be obtained with the smallest PS diameter of 392 nm and 180 s WO3 electrodeposition. In its colored state, the 392‐SnO2 –WO3 ‐180 core–shell IO structure shows ≈70% visible light transparency, 62% NIR blockage at 1200 nm, and ≈15% drop in NIR blocking stability after 300 cycles. The SnO2 –WO3 core–shell IO structure in this study is a promising EC material for advanced smart window technology. Abstract : Hybrid SnO2 –WO3 core–shell inverse opal structure is obtained by electrodeposition of amorphous WO3 electrochromic layer on highly transparent SnO2 inverse opal framework. As‐fabricated SnO2 –WO3 core–shell inverse opal structure with initial pore size of 392 nm demonstrates the optimal visible transparency (about 70% at colored state) and near‐infrared contrast (62% at 1200 nm).